Immunomodulatory biomaterials on chemokine signaling in wound healing - Apte, Anisha; Liechty, Kenneth W.; Zgheib, Carlos (Frontiers in Pharmacology, 2023)
Normal wound healing occurs through a careful orchestration of cytokine and chemokine signaling in response to injury. Chemokines are a small family of chemotactic cytokines that are secreted by immune cells in response to injury and are primarily responsible for recruiting appropriate immune cell types to injured tissue at the appropriate time (1). Dysregulation of chemokine signaling is suspected to contribute to delayed wound healing and chronic wounds in diseased states. Various biomaterials are being used in the development of new therapeutics for wound healing and our understanding of their effects on chemokine signaling is limited. It has been shown that modifications to the physiochemical properties of biomaterials can affect the body’s immune reaction. Studying these effects on chemokine expression by various tissues and cell type can help us develop novel biomaterial therapies. In this review, we summarize the current research available on both natural and synthetic biomaterials and their effects on chemokine signaling in wound healing. In our investigation, we conclude that our knowledge of chemokines is still limited and that many in fact share both pro-inflammatory and anti-inflammatory properties. The predominance of either a pro-inflammatory or anti-inflammatory profile is mostly likely dependent on timing after injury and exposure to the biomaterial. More research is needed to better understand the interaction and contribution of biomaterials to chemokine activity in wound healing and their immunomodulatory effects.